2001
DOI: 10.1053/euhj.2000.2366
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and long-term follow-up of the Brugada syndrome in patients with idiopathic ventricular fibrillation

Abstract: Depending on the diagnostic criteria used, the Brugada syndrome was observed in 3% to 24% of patients with idiopathic ventricular fibrillation, underlining the importance of defining the precise diagnostic criteria in these patients. For all idiopathic ventricular fibrillation patients, the ventricular tachyarrhythmia recurrence rate was substantial during an average follow-up of more than 6 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
49
0
3

Year Published

2002
2002
2006
2006

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 14 publications
7
49
0
3
Order By: Relevance
“…10 This consensus is supported by our observation that a previous cardiac arrest is a strong indicator of adverse outcome, yet treatment of most asymptomatic individuals with a Brugada ECG or patients with syncope remains less clear. Following the recommendations of Brugada et al, 2 implantation of a defibrillator in patients with a previous syncope and a type 1 ECG "seems to be as mandatory as it is in patients with resuscitated sudden arrhythmic death."…”
Section: Treatment Strategy In Individuals With a Brugada Ecgsupporting
confidence: 58%
“…10 This consensus is supported by our observation that a previous cardiac arrest is a strong indicator of adverse outcome, yet treatment of most asymptomatic individuals with a Brugada ECG or patients with syncope remains less clear. Following the recommendations of Brugada et al, 2 implantation of a defibrillator in patients with a previous syncope and a type 1 ECG "seems to be as mandatory as it is in patients with resuscitated sudden arrhythmic death."…”
Section: Treatment Strategy In Individuals With a Brugada Ecgsupporting
confidence: 58%
“…The electrocardiographic signature of the syndrome is dynamic and often concealed, but can be unmasked by potent sodium channel blockers such as flecainide, ajmaline, and procainamide, 7 although the specificity of this effect for uncovering patients at risk for sudden death has been an issue of concern. A recent report by Remme et al 8 has shown that the number of idiopathic ventricular fibrillation patients diagnosed as having Brugada syndrome is a sensitive function of the diagnostic criteria applied. What are the proper diagnostic criteria for identifying Brugada syndrome?…”
mentioning
confidence: 99%
“…This condition, known as Brugada syndrome, accounts for Ϸ20% to 30% of cases previously diagnosed as idiopathic ventricular fibrillation. 2 The pathophysiology of this syndrome remains poorly understood. In 1998, Chen et al 3 discovered the first genetic defect, a mutation in the cardiac sodium channel gene SCN5A.…”
mentioning
confidence: 99%